Response of fermentation quality and microbial community of oat silage to homofermentative lactic acid bacteria inoculation - Tahir, Muhammad; Li, Jiayi; Xin, Yafen; Wang, Tianwei; Chen, Chen; Zhong, Yihao; Zhang, Lei; Liu, Haiping; He, Yaling; Wen, Xingjin; Yan, Yanhong (Frontiers in Microbiology, 2023)
Oat (Avena sativa L.) is one of the important forage crops in the world. Meanwhile, oat grown in Southwest China has higher moisture content and its preservation face significant challenges. Moreover, existing commercial lactic acid bacteria (LAB) have poor fermentation effect in hot and humid regions. Consequently, current study investigated the response of oat fermentation quality and microbial community to self-selected LAB inoculation. The treatments were: CK, sterilized water; LP694, Lactobacillus plantarum 694; LR753, Lactobacillus rhamnosus 753; and LPLR, LP694 combined with LR753, followed by 1, 3, 7, 14, and 60 days (d) of fermentation. Results showed that LAB inoculation significantly raised the lactic acid content, and decreased the level of pH value, acetic acid and ammonia-N in oat silage. The LR753 group had significant higher (p < 0.05) lactic acid content (60.95 g kg−1 DM−1), and lower pH value (3.95), and ammonia-N content (10.1 g kg−1 DM−1) followed by LPLR group. The LR753 showed lower NDF (54.60 %DM) and ADF (39.73 %DM) contents than other groups. The Latobacillus was prevalent genus in LAB treated groups, and its relative abundance reached maximum in LP694 (69%) on 3 d, while in LR753 group (72%) on 60 d. The Lactobacillus rhamnosus, Lactobacillus plantarum, and Lactobacillus fermentum became the dominant species in LAB treated groups with fermentation time. The Lactobacillus genus was positively correlated with WSC (R = 0.6, p < 0.05), while negatively correlated with pH (R= -0.5, p < 0.05), and BA (R = -0.5, p < 0.01). Overall, LR753 group had better fermentation quality and preservation of nutritional components providing the theoretical support and guidance for future oat silage production in southwest China.